SOCIO-PHILOSOPHICAL ANALYSIS OF THE CONCEPT OF SPIRITUAL DEVELOPMENT - Suleymanov Sarvar Sunatullayevich (Bright Mind Publishing, 2026)
This article provides a socio-philosophical analysis of the concept of spiritual development. It illuminates issues related to national self-realization and the creation of an ideological foundation for the spiritual development of New Uzbekistan, based on national characteristics and harmonized with universal human values.
Keywords: Spiritual development, spiritual ascent, national self-awareness, values, cultural heritage, customs.